2023
DOI: 10.1037/sah0000375
|View full text |Cite
|
Sign up to set email alerts
|

The negative health effects of anti-Asian stigma in the U.S. during COVID-19.

Abstract: This study provided a systemic review of the content of 50 behavioral and social science studies investigating enactment and outcomes of anti-Asian stigma related to coronavirus disease (COVID-19) published in the final quarter of 2020 and during 2021. Based on a systematic search of several databases in December of 2021, 500 studies describing the impact of COVID-related stigma on Asian Americans were identified. From this group, 50 studies meeting the inclusion criteria were analyzed focusing on health and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Lastly, the generalizability of our findings needs validation through an independent dataset. For example, Asians, who have reportedly faced frequent COVID-19related discrimination [81][82][83] , represent only 0.5% of our study sample. This racial imbalance within the ABCD dataset could limit the representativeness of our results.…”
Section: Discussionmentioning
confidence: 96%
“…Lastly, the generalizability of our findings needs validation through an independent dataset. For example, Asians, who have reportedly faced frequent COVID-19related discrimination [81][82][83] , represent only 0.5% of our study sample. This racial imbalance within the ABCD dataset could limit the representativeness of our results.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Hahm et al (2021) suggested that increases in COVID-19 related discrimination may be more strongly associated with post-traumatic stress disorder symptoms (e.g., disturbed memories, thoughts, and avoidance) than anxiety symptoms. Finally, a systematic review outlined the overall health consequences of the anti-Asian stigma on Asian Americans and emphasized mental health concerns (e.g., increased levels of anxiety, fear for personal safety and for loved ones), social health concerns (e.g., increased microaggressions, model-minority stereotypes endorsements, shunning behavior by others), and physical health concerns (e.g., headaches, heart palpitations) (Bresnahan et al, 2022).…”
Section: Anti-asian Racism and Health Impactsmentioning
confidence: 99%
“…Mass media can have their own financial and political interests in stigmatization as it may attract more "eyeballs" in the attention economy (REF). Also, mass media may frame a group of people in a negative light due to their political interests leading to prejudice and discrimination against these people, like the example of stigma against Asians in the COVID-19 pandemic [27]. Moreover, HIV/AIDS is associated with social interaction difficulties and seclusion [1,11] that may negatively affect the efficacy of mass media programs in reducing HIV-related stigma.…”
Section: Introductionmentioning
confidence: 99%